ПЕДАГОГІЧНЕ УПРАВЛІННЯ СТВОРЕННЯМ ДИДАКТИЧНИХ ШЛЯХІВ ДО ОСОБИСТОСТІ УЧНЯ У НАВЧАЛЬНО-ВИХОВНОМУ ПРОЦЕСІ (Педагогіка вищої та середньої школи, 2002)
The system of the pedagogical ruling by the creation of the didactic steps up to the personality of the pupil in the educational the process may be rather effective if the pedagogical help of the personality, the understanding, the unity of the teacher and the pupil is provided; the individuality of the child, the individual achieve with the usage of the pedagogical foreseen and pedagogical technologies are accounted.